METHANE IN GROUND ICE AND FROZEN SEDIMENTS IN THE COASTAL ZONE AND ON THE SHELF OF KARA SEA - I. D. Streletskaya; A. A. Vasiliev; G. E. Oblogov; P. B. Semenov; B. G. Vanshtein; E. M. Rivkina (Лëд и снег, 2018)
Summary Degradation of permafrost on the continental shelf and shores of the Arctic seas may be a main cause of the methane emission to the atmosphere from marine sediments. To quantify this effect it is necessary to have reliable data on the methane content in the underground ice and frozen Quaternary deposits. Samples of frozen (permafrost) sediments and ground ice, taken in three reference coastal sections made in the Mid- and Late Pleistocene coastal exposures and on the Kara sea shelf, were collected and studied. The samples were analyzed to determine composition, salinity, organic carbon content, and other characteristics of the underground ices. About 270 samples allowed determination of the gas composition and the methane concentration. The gas is present in the pores of the rocks and air bubbles in the ice. Gas was present in pores of sediments and in bubbles within the ice. It has been established that the composition of non-hydrocarbon gases in the underground ice does not correspond to the composition of the atmosphere in the time of formation of them. The methane content in the underground ice and frozen sediments is characterized by very high variability. The highest concentrations of methane are inherent in layers of the massive ground ice and reach up to 23000 ppm; the maximum concentration of methane in the massive vein ices does not exceed 900 ppm. High concentrations of methane in layers of the massive ice confirm their non-glacier formation. The highest, up to 6400 ppm, methane concentrations in permafrost sediments are characteristic for the Late Pleistocene marine clays, while in the Mid Pleistocene marine clays it does not exceed 1700 ppm. The isotopic composition of methane in frozen sediments and ground ice in both, the Cara Sea coast and shelf, is indicative of similar bacterial genesis of the gas. The total organic carbon content plays the limiting role in the methane production and its accumulation in the frozen sediments and ground ice.